The COVID-19 Panic and the Strengthening of Team Spirit to Combat Pandemic - Voo, Peter; Ationg, Romzi; Zakaria, Suwaibah; Maakip, Ismail; A. Malek, Mohd. Dahlan Hj. (Asian Social Work Journal, 2024)
The outbreak of respiratory disease caused by COVID-19 brings a significant impact towards various areas of human life such as the growing panic among the populations. Accordingly, the Movement Control Order (MCO) has been executed by the governments around the globe to prevent the citizens from getting infected, thus lessening the panic. Therefore, during the MCO there appears to be a great opportunity for the consolidation of team spirit among the citizens. This is especially true in Malaysia where it seems that although the disease is mainly a medical issue, it also prevails the way the citizens eradicate panic and strengthening the team spirit. It is argued that though the disease brings problems, the outbreak provides opportunities for a more thorough way of eradicating panic and strengthening team spirit among the citizens. This paper presents a preliminary discussion on the method of eradicating panic and strengthening team spirits for combating pandemic among the citizens of Sabah, Malaysia. The study in which this paper is based applies a qualitative method of document and media social analysis. It thus unveils the prospects of eradicating COVID-19 panic and strengthening team spirit among the citizens.